Community Participation in Waste Management in Luangprabang World Heritage Town - SOMSAMONE, Vilayphone; SIFONGXAY, Sangthong; SOULIYASACK, Somkit; ONKEO , Sengla; BOUNPATHAPH, Latsamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The objectives of this study were to: 1) study current state of waste management in the community in Luang Prabang world heritage town, 2) analyze the varying degrees of community participation in waste management in Luangprabang world heritage town, 3) compare the difference between factors of participation and the varying degrees of community participation in waste management in Luangprabang world heritage town. Data was collected through a set of questionnaires that were distributed among 486 representative of households in the world heritage area, Luang Prabang district, Luang Prabang province. The obtained data was then analyzed by using the Statistical Package for the Social Sciences Program. Research results revealed that the waste management community 5R principles applied by households were: waste reduction by buying high quality products and keeping them as long as possible, the use of reusable bags, use of table napkins or hand towels to replace tissue paper and the use of refillable products. There was also waste recycling by composting waste and returning it to the soil, the reuse of glass bottles or plastic bottles for drinking water and the donation or sale of the things that you do not use. Another form of waste management was the repairing of clothes, furniture and broken electrical equipment rather than throwing it away to purchase new ones. There was also the use of kindling (small sticks of wood) to make a fire to cook food, and using tires for planting flowers and vegetables. Waste was also recycled by sorting and placing in the right bags for collection, which could then be sold. Another way was by rejecting the once only use of products in stores, such as plastic bags and foam boxes. However, the community participation on waste management in Luangprabang world heritage town there was found to be at the same level. The comparison of results of community participation on waste management, found the different personal factors of respondents such as gender, age, status, education, occupation and monthly income had little statistical significance on participation with a 0.05 level.